A comparative study on the Village – Town Distinction in Thenmaradchi Region: With Special Reference to J/302 and J/343 Divisional Areas - Ravishankar, V.; Janarthani, B. (University of Jaffna, 2014)
The development of area is the most important part in this 21th century when the world countries have come under the globalization. The difference between the village and the town is an obstruction for the development of area. The development of the village is considered as the development of the nation since the share of the villages is more than the share of the town in extent and population. The village is meant that an area or colony consisting of cottage or houses, made by the people for their existence during the gradual civilization of the humanity. But the town is meant a large human colony where various people live together and it bears certain qualities. The Thenmaradchchi area was researched utilizing the simple random model technique. The village of Sankaththanani (J/302), located nearest to Chavakachcheri town, which was considered as town and the village of varany iyattalai (J/343) which is considered as a highly populated remote village was taken for research utilizing the simple random model technique. The impotent problem of this research is the difference between the town and village, which is an obstruction for the development of this area. This is to say the difference between the village and the town in utilizing the resources and the availability of same, which is viewed on the ground of economic or non – economic factor, paves way for the impediment of the development of village and town areas. Thereby, the social and economic differences between the people of the village and town creates lot of problems such as inequality in income, poverty, unemployment, inequality of resources and less development. It is impossible to reach the development of thenmaradchchi area since the difference between the town and village leads for the economical imbalance and the inequality of the social and economic standard. This research was resorted on the gourd of the difference between the town and village. The main aim of this research is to find out the social and economic difference between the people of town and village of J/302 and J/343. The dates were collected by issuing questionnaires, discussion and based on secondary information. It is observed that there is economical difference between the town and village in Thenmaradchchi area. This difference is considered as hypothesis 1(H1). The non- economical difference between the village and town in thenmaradchchi area is considered as hypothesis 2(H2). For this research, all the data were analyzed through SPSS and a clear result was obtained. The study found that there are economical and non- economical difference between the village and town of Thenmaradchchi region.
Keywords: the village – town distinction; economic factors; non- economic factors; availability of resources; utilizing of resources